Answer:
56
Step-by-step explanation:
447/8
56
well actually
55.875
I just rounded it up
The answer is 2. hope thishelps
Answers:
1) Given
2) angle 2 ** see note below
3) angle 3 ** see note below
4) converse of alternate exterior angle theorem
note: you can swap the answers for 2 and 3 and it doesn't matter
========================================================
Explanations:
1) This is given so we just simply state "given". It seems silly to repeat what is given, but this is how you start any geometry proof.
2 & 3) The answers here are angle 2 and angle 3 because they are both interior angles (on the inside of the parallel lines m and L) and they are on alternate sides of the transversal line q. So they are both alternate interior angles and are congruent due to line L parallel to line m (alternate interior angle theorem)
4) If you have a pair of parallel lines, then the alternate exterior angle theorem says that alternate exterior angles are congruent. Going in reverse, the converse of this theorem says that having a pair of congruent alternate exterior angles (angle 1, angle 2) leads to the lines being parallel (p and q).
Answer:
second option
Step-by-step explanation:
Using the rule of radicals
×
⇔ ![\sqrt{ab}](https://tex.z-dn.net/?f=%5Csqrt%7Bab%7D)
Simplifying the radicals
![\sqrt{27x^{3} }](https://tex.z-dn.net/?f=%5Csqrt%7B27x%5E%7B3%7D%20%7D)
= ![\sqrt{9(3)x^2.x}](https://tex.z-dn.net/?f=%5Csqrt%7B9%283%29x%5E2.x%7D)
=
×
×
× ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
= 3 ×
× x × ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
= 3x![\sqrt{3x}](https://tex.z-dn.net/?f=%5Csqrt%7B3x%7D)
-------------------------------
![\sqrt{12x^{3} }](https://tex.z-dn.net/?f=%5Csqrt%7B12x%5E%7B3%7D%20%7D)
= ![\sqrt{4(3)x^2.x}](https://tex.z-dn.net/?f=%5Csqrt%7B4%283%29x%5E2.x%7D)
=
×
×
× ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
= 2 ×
× x × ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
= 2x![\sqrt{3x}](https://tex.z-dn.net/?f=%5Csqrt%7B3x%7D)
---------------------------------------
Thus
3 × 3x
- 2 × 2x![\sqrt{3x}](https://tex.z-dn.net/?f=%5Csqrt%7B3x%7D)
= 9x
- 4x![\sqrt{3x}](https://tex.z-dn.net/?f=%5Csqrt%7B3x%7D)
= 5x